Do Enclaves Matter in Immigrant Adjustment? - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2002)
This paper is concerned with the determinants and consequences of immigrant/linguistic concentrations (enclaves). The reasons for the formation of these concentrations are discussed. Hypotheses are developed regarding ?ethnic goods? and the effect of concentrations on the immigrant?s language skills, as well as the effects on immigrant earnings of destination language skills and the linguistic concentration. These hypotheses are tested using PUMS data from the 1990 U.S. Census on adult male immigrants from non-English speaking countries. Linguistic concentrations reduce the immigrant?s own English language skills. Moreover, immigrant?s earnings are lower the lower their English-language proficiency and the greater the linguistic concentration in their origin language of the area in which they live. The adverse effects on earnings of poor destination language skills and of immigrant concentrations exist independently of each other.
Keywords: J15; J61; J31; J24; 330; Immigrants; earnings; language skills; enclaves; ethnic/immigrant concentrations; ethnic goods; United States; Migranten; Wohnstandort; Sprache; Qualifikation; Agglomerationseffekt; Vereinigte Staaten